Microtomographic Analysis of Impact Damage in FRP Composite Laminates: A Comparative Study. (30th May 2013) - Alemi-Ardakani, M.; Milani, A. S.; Yannacopoulos, S.; Bichler, L.; Trudel-Boucher, D.; Shokouhi, G.; Borazghi, H.
Abstract : With the advancement of testing tools, the ability to characterize mechanical properties of fiber reinforced polymer (FRP) composites under extreme loading scenarios has allowed designers to use these materials in high-level applications more confidently. Conventionally, impact characterization of composite materials is studied via nondestructive techniques such as ultrasonic C-scanning, infrared thermography, X-ray, and acoustography. None of these techniques, however, enable 3D microscale visualization of the damage at different layers of composite laminates. In this paper, a 3D microtomographic technique has been employed to visualize and compare impact damage modes in a set of thermoplastic laminates. The test samples were made of commingled polypropylene (PP) and glass fibers with two different architectures, including the plain woven and unidirectional. Impact testing using a drop-weight tower, followed by postimpact four-point flexural testing and nondestructive tomographic analysis demonstrated a close relationship between the type of fibre architecture and the induced impact damage mechanisms and their extensions.